Care About Old Persons in the Social Protection System of the Republic of Serbia - Simatković, Mina B. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The prolongation of lifespan determines the position of old people in modern society. Therefore, age problems become a significant social phenomenon that seizes the scientific and professional attention of gerontologists, geriatrics, sociologists, social workers, criminologists, psychologists, and others. We live in a time of political and economic crises and changes in which there are categories of the population that are endangered, impoverished, sick, lonely, vulnerable, which is especially pronounced in the old population. Although, in our country, care for the elderly is largely reduced to the family and has a multi-generational character. More and more, the family is unable to bear the burden of that care alone. Many old people live alone or in nursing homes, since young people have left the country and parents in search of a better life for the past twenty years. Through the legal solutions and the Strategy on the old, the Republic of Serbia is trying, through institutional and non-institutional forms of protection, to help people of the third age.
Keywords: non-institutional protection; institutional protection; re-socialization; socialization; social integration; aging; age